Reinfection of farm dogs following praziquantel treatment in an endemic region of cystic echinococcosis in southeastern Iran. - Mehdi Borhani; Mohammad Ali Mohammadi; Mahbod Entezami; Mohammad Reza Baneshi; Saeid Nasibi; Joaquin M Prada; Majid Fasihi Harandi (Public Library of Science (PLoS), 2024)
Cystic Echinococcosis (CE) as a prevalent tapeworm infection of human and herbivorous animals worldwide, is caused by accidental ingestion of Echinococcus granulosus eggs excreted from infected dogs. CE is endemic in the Middle East and North Africa, and is considered as an important parasitic zoonosis in Iran. It is transmitted between dogs as the primary definitive host and different livestock species as the intermediate hosts. One of the most important measures for CE control is dog deworming with praziquantel. Due to the frequent reinfection of dogs, intensive deworming campaigns are critical for breaking CE transmission. Dog reinfection rate could be used as an indicator of the intensity of local CE transmission in endemic areas. However, our knowledge on the extent of reinfection in the endemic regions is poor. The purpose of the present study was to determine E. granulosus reinfection rate after praziquantel administration in a population of owned dogs in Kerman, Iran. A cohort of 150 owned dogs was recruited, with stool samples collected before praziquantel administration as a single oral dose of 5 mg/kg. The re-samplings of the owned dogs were performed at 2, 5 and 12 months following initial praziquantel administration. Stool samples were examined microscopically using Willis flotation method. Genomic DNA was extracted, and E. granulosus sensu lato-specific primers were used to PCR-amplify a 133-bp fragment of a repeat unit of the parasite genome. Survival analysis was performed using Kaplan-Meier method to calculate cumulative survival rates, which is used here to capture reinfection dynamics, and monthly incidence of infection, capturing also the spatial distribution of disease risk. Results of survival analysis showed 8, 12 and 17% total reinfection rates in 2, 5 and 12 months following initial praziquantel administration, respectively, indicating that 92, 88 and 83% of the dogs had no detectable infection in that same time periods. The monthly incidence of reinfection in total owned dog population was estimated at 1.5% (95% CI 1.0-2.1). The results showed that the prevalence of echinococcosis in owned dogs, using copro-PCR assay was 42.6%. However, using conventional microscopy, 8% of fecal samples were positive for taeniid eggs. Our results suggest that regular treatment of the dog population with praziquantel every 60 days is ideal, however the frequency of dog dosing faces major logistics and cost challenges, threatening the sustainability of control programs. Understanding the nature and extent of dog reinfection in the endemic areas is essential for successful implementation of control programs and understanding patterns of CE transmission.